2018
DOI: 10.1016/j.fpsl.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Quality of fresh saithe (Pollachius virens) in modified atmosphere packages as affected by the gas composition

Abstract: The experimental design was set up to study the effect of different modified atmospheres (CO2 (67 or 33%) balanced with either O2 or N2) on autolytic-and microbiological deterioration of chilled saithe (Pollachius virens). As controls, vacuum packaged saithe was used. The results showed a positive effect of gas mixtures containing O2 on physiochemical and microbial product quality. Discriminating factors were; lower psychrotrophic count, slower breakdown of ATP, lower contents of certain biogenic amines (e.g. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Lerfall et al [ 27 ] evaluated the growth changes of pseudomonads at 4 °C in different modified atmospheres in saithe and reported a growth of 3 logs in low CO 2 /high O 2 fish samples (31.3% CO 2 /66.0% O 2 /2.7% N 2 ) only, whereas in the other gas combinations assayed, no growth could be detected. Koutsoumanis et al [ 25 ] studied the combined effect of storage temperature and packaging conditions (air and MAP) on red mullet and reported that the main spoilage bacteria in air were Pseudomonas spp.…”
Section: Resultsmentioning
confidence: 99%
“…Lerfall et al [ 27 ] evaluated the growth changes of pseudomonads at 4 °C in different modified atmospheres in saithe and reported a growth of 3 logs in low CO 2 /high O 2 fish samples (31.3% CO 2 /66.0% O 2 /2.7% N 2 ) only, whereas in the other gas combinations assayed, no growth could be detected. Koutsoumanis et al [ 25 ] studied the combined effect of storage temperature and packaging conditions (air and MAP) on red mullet and reported that the main spoilage bacteria in air were Pseudomonas spp.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most common practices of the first strategy is to choose the sensory rejection of control and treated group as two vital points and compared them with each other (C–I) (Huang et al., 2017; Jia, Huang, et al. 2018, Jia, Liu, et al., 2018; Lerfall et al., 2018; Liu, X., Li, D., et al., 2018; Parlapani et al., 2020), although the sensory rejection of control and treated group is not on the same day. Nevertheless, some preservatives could retard the microbiota succession and the formation of SSOs’ dominance, whereas having less effect on the final microbial community when products get spoiled.…”
Section: Methods and Technologies Used In Microbiota Characterizationmentioning
confidence: 99%
“…First of all, composition of the initial microbiota and SSOs largely depends on the water habitat in which fish and crustaceans live (Ghaly, Dave, Budge, & Brooks, 2010). For example, Photobacterium especially Photobacterium phosphoreum usually associate with the spoilage of vacuum or modified atmosphere packed seafood like finfish (Dalgaard, 1995; Emborg, Laursen, Rathjen, & Dalgaard, 2002; Hansen, Mørkøre, Rudi, Olsen, & Eie, 2007; Jääskeläinen et al., 2019; Kuuliala et al., 2018; Lerfall, Thomassen, & Jakobsen, 2018; Odeyemi et al., 2018; Sørensen et al., 2020) and lobsters (Gornik, Albalat, Macpherson, Birkbeck, & Neil, 2011), while they are scarcely detected in freshwater fish/crustacean species. S. baltica is widely considered as a strong spoiler of chilled seafood (Gu et al., 2013; Vogel, Venkateswaran, Satomi, & Gram, 2005; Zhao, A., et al., 2016).…”
Section: Influencing Factors Of Microbiota Composition In Fish and Crmentioning
confidence: 99%
See 1 more Smart Citation
“…Degradation products of adenosine triphosphate (ATP) were analyzed on a Phenomenex synergi 4u hydro‐RP80 A (150 × 4.6 mm, 4 µm) HPLC column after a method by Sellevold, Jynge, and Aarstad (), using an Agilent 1290 chromatograph (Agilent Technologies, Paolo Alto, CA, USA) (isocratic, flow 1.0 mL × min −1 ) connected to an Agilent 1260 diode array UV‐VIS detector, as described by Lerfall, Jakobsen, and Bjørge Thomassen (). Standard curves of ATP (Sigma, ≥99%, CAS:34369‐07‐8), ADP (Sigma, ≥95%, CAS:20398‐34‐9), AMP (Sigma, ≥99%, CAS:149022‐20‐8), IMP (Sigma, ≥98%, CAS:352195‐40‐5), HxR (Sigma, ≥99%, CAS:58‐63‐9), and Hx (Sigma, ≥99.0% CAS:68‐94‐0) in deionized water were used for identification of quantification.…”
Section: Methodsmentioning
confidence: 99%